PROFIL PERUBAHAN AMONIUM, NITRIT DAN NITRAT PADA PERCOBAAN CURAH DARI PDAM BOGOR DAN SURABAYA - Hartati Imamuddin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Nitrification is often not effective because the characters of nitrifying bacteria is always slow growing and temperature, pH, DO, amonia concentration, nitrite and C/N ratio as the limited factors. Batch experiment was operated for 6 hours, every half an hours ammonium, nitrite and nitrate were measured.The results showed that added C sourse (glucose) in medium from PDAM Bogorand Surabaya have a significant effects of ammonium degradation, nitrite and nitrate production. Degradation of ammonium in batch reactor from PDAM Bogor showed that both naerobic and aerobic condition have a different fluctuation. Production of nitrite was stable from the middle of reaction to last of aerobic phase. In aerobic condition nitrate production is reduced to 49,21 % (+ glucose) and 60,87% (+ acetate) Batch reactor from PDAM Surabaya differ from PDAM Bogor particularly on degradation of ammonium. Added glucose as C source cause the concentration of ammonium was increased and acetate as C source showed stable with a slightly fluctuation. Nitrite and nitrate production relatively small in both C source.